S-310JA-2 デ カンソク サレタ VLF ヒス ノ トクセイ c. ハドウ リュウシ ソウゴ サヨウ ダイ1カイ キョクチ ニオケル デンリケン ジキ ソウゴウ カンソク シンポジウム PART 2 - 松尾, 敏郎; マツオ, トシロウ; 木村, 磐根; キムラ, イワネ; 鎌田, 哲夫; カマタ, テツオ; MATSUO, Toshiro; KIMURA, Iwane; KAMATA, Tetsuo (国立極地研究所, 1979)
P(論文) VLF帯(02～10kHz)電波観測器を搭載したS-310JA-2号機によりVLFヒスが観測された.このヒスは磁界(H)セソサーては観測されす,電界(E)センサーのみに観測され,しかもその下限のカットオフがシャープで,かつその周波数がロケット近傍のLHR周波数と一致すると推定されることから,このヒスはLHRヒスと考えられ,もしそうだとするとロケット観測ては初めての観測である.ヒスの7kHz成分の強度とシースインピータンスの高度プロファイルも得られた. VLF hiss was observed on the S-310JA-2 rocket at Syowa Station in the Antarctic region (69°00'S, 39°35' E) at 03 22 LT on February 10, 1977, during polar magnetic storm (ΔH, -680γ) This hiss was observed only with a 24 m tip-to-tip electric dipole antenna, not observed with a ferrite core loop antenna, and exhibited a sharp lower cut-off frequency which seemed to be associated with lowerhybrid resonance (LHR) in the vicinity of rocket, If we assume the ion composition and electron density. at the observing altitude. Therefore it may be the first rocket observation of LHR hiss. We also obtained altitude profiles of sheath impedance and 7 kHz hiss strength. departmental bulletin paper